THE PECULIARITIES OF ACCUMULATION OF COLLAGENS I AND III TYPES AND ELASTIN IN THE LIGAMENTS OF THE UTERUS WHEN THE PROLAPSE GENIALI (IMMUNOHISTOCHEMISTRY) - V. E. Radzinskiy; M. L. Khanzadyan; T. A. Demura; R. Cоnnon (Медицинский вестник Юга России, 2014)
Purpose: to study the molecular and biochemical changes underlying the PG and immunohistochemical characteristics of accumulation of collagens I and III and elastin in the sacro-uterine and round ligaments of the uterus at PG.Materials and methods: the examined 15 patients aged from 42 to 65 years with full and partial prolapse of the uterus and vaginal walls, which have had a hysterectomy vaginal access. The control group consisted of 15 women ranging in age from 35 to 52 years with no signs of GHGs, which have had a hysterectomy abdominal access for uterine fibroids, adenomyosis, endometrial pathology. All patients were comparable in parieto birth. In the groups evaluated the results of morphological and immunohistochemical research biopsies of the sacro-uterine and round ligaments.